2003
DOI: 10.1097/01.asn.0000081698.10331.83
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dyslipidemia in End-Stage Renal Disease

Abstract: Abstract. Heart disease is a major cause of morbidity and mortality among patients with renal failure. Premature atherosclerotic coronary heart disease is driven by multiple risk factors, including dyslipidemia and oxidative stress. In the nondialysis population, there is overwhelming evidence that treatment of dyslipidemia can significantly improve cardiovascular outcomes. Accumulating data indicate that dialysis patients have atherogenic lipid abnormalities. Although LDL cholesterol (LDL-C) levels in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 41 publications
4
59
0
3
Order By: Relevance
“…This is in accordance with other reports, which show that patients with end-stage renal disease have low levels of HDL-C and increased levels of very-low density lipoprotein (VLDL) and intermediate-density lipoprotein (IDL), leading to elevated triglyceride levels. 22,23 We also found that in the PD group, patients have higher cholesterol and Apo-B levels than in HD group, as reported previously. 7,24,25 A possible explanation for this abnormality is the exposure of patients to glucose in the dialysate and insulin resistance that activates the delivery of free fatty acids (FFAs) to the liver and subsequently the oxidation or esterification of FFAs to cytosolic triglycerides or VLDL.…”
Section: Discussionsupporting
confidence: 89%
“…This is in accordance with other reports, which show that patients with end-stage renal disease have low levels of HDL-C and increased levels of very-low density lipoprotein (VLDL) and intermediate-density lipoprotein (IDL), leading to elevated triglyceride levels. 22,23 We also found that in the PD group, patients have higher cholesterol and Apo-B levels than in HD group, as reported previously. 7,24,25 A possible explanation for this abnormality is the exposure of patients to glucose in the dialysate and insulin resistance that activates the delivery of free fatty acids (FFAs) to the liver and subsequently the oxidation or esterification of FFAs to cytosolic triglycerides or VLDL.…”
Section: Discussionsupporting
confidence: 89%
“…This may partially explain why the association between fetuin A and dyslipidemia occurs mainly on the non-HDL-C and TG components. On the relationship between dyslipidemia and CV mortality (29)(30)(31), the relationship between high fetuin A and CV mortality warrants further investigation through larger studies because its reverse impact on CV mortality related to malnutrition and CV calcification in dialysis patients has been shown in previous studies (3,18).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, fibrates can cause a hemodynamic decrease in GFR (29) and are used with caution in patients with CKD. Physicians may also be more reluctant to prescribe lipid-lowering agents to a patient population in whom a clear benefit from these drugs has never been shown (30,31) and who often have polypharmacy, increasing the risk of drug interactions and side effects (32,33). Although many reasons can explain the differences we observed, physicians should keep in mind that subgroup analyses from randomized controlled trials clearly show a beneficial effect of statins in the prevention of future cardiovascular events in subjects with moderate kidney dysfunction (34,35).…”
Section: Discussionmentioning
confidence: 99%